Holocaust consciousness and Cold War violence in Latin America - Tarica, Estelle (State University of New York Press, 2022)
Examines how community leaders, writers, and political activists facing state repression in Latin America have drawn on and debated the validity of Holocaust terms to describe human rights atrocities in their own countries.
Description based upon print version of record.
Keywords: Holocaust, Jewish (1939-1945) -- Foreign public opinion, Latin American.; Politics and culture -- Latin America -- History -- 20th century.; State-sponsored terrorism -- Latin America -- History -- 20th century.; Genocide -- Latin America -- History -- 20th century.; Latin America -- Politics and government -- 1948-1980.; Collective memory -- Argentina.; Collective memory -- Guatemala.; Collective memory -- Mexico.; Politique et culture -- Amérique latine -- Histoire -- 20e siècle.; Terrorisme d'État -- Amérique latine -- Histoire -- 20e siècle.; Amérique latine -- Politique et gouvernement -- 1948-1980.; Mémoire collective -- Argentine.; Mémoire collective -- Guatemala.; Mémoire collective -- Mexique.; LITERARY CRITICISM / Caribbean & Latin American.; Collective memory; Genocide; Politics and culture; Politics and government; Public opinion, Latin American; State-sponsored terrorism; Argentina; Guatemala; Latin America; Mexico; 1900-1999; History; Literary criticism.; Critiques littéraires.